Elastoplastic behavior of compacted kaolin under consolidated drained and shearing infiltration conditions - Kim, Yongmin (2019)
This study presents a comprehensive laboratory study to characterize the elastoplastic behavior of compacted kaolin under consolidated drained (CD) and shearing-infiltration (SI) triaxial conditions. The laboratory tests include a soil-water characteristic curve (SWCC), isotropic consolidation (IC), CD, and SI tests under different net confining stresses to consider in situ stress state and matric suctions that describe the volume change characteristics of unsaturated soil with respect to two stress state variables (i.e., net normal stress and matric suction). Consistently prepared specimens of statically compacted kaolin were used in this study. The results of the SWCC tests demonstrated that the air-entry value and yield suction (so) increased with an increase in net confining stress. The IC tests indicated the strong influence of matric suction on compressibility and stiffness of the compacted kaolin. The results of SI tests indicated that water infiltration reduced the matric suction of the soil and was accompanied by a degradation in deviator stress. It was also found from the CD and SI tests that the failure envelope of compacted kaolin was unique. For practical purposes of transient analyses, therefore, the CD and SI tests, as well as the SWCC and IC tests, might be performed to obtain more rigorously elastoplastic behavior of unsaturated soil under CD and SI conditions.